Observations of convectively coupled Kelvin waves - Straub, Katherine H., author; Schubert, Wayne, advisor; Randall, David, committee member; Johnson, Richard, committee member; Thomas, J. W., committee member; Kiladis, George, committee member (Colorado State University. Libraries, 2002)
Convectively coupled Kelvin waves are large-scale, eastward-propagating tropical convective disturbances with the dispersion characteristics of equatorially trapped shallow water Kelvin modes. Convection in these waves propagates eastward at 15-20 m s-1, with a horizontal scale of approximately 3000 km, and is accompanied by large-scale dynamical perturbations in the troposphere and lower stratosphere that are broadly consistent with linear equatorial wave theory.

Observations of convectively coupled Kelvin waves are presented based on statistical composites of global reanalysis and radiosonde data and a case study from the 1997 Tropical Eastern Pacific Process Study (TEPPS). These observations address several important issues regarding the horizontal and vertical structure of Kelvin waves, the mechanisms for their initiation, and their modulation by intraseasonal variability.

The TEPPS case study provides detailed information about the small-scale structure observed during the passage of a convectively coupled Kelvin wave in the eastern Pacific intertropical convergence zone (ITCZ). Convection is organized within the eastward-propagating envelope into smaller-scale westward-propagating cloud clusters, in which stratiform precipitation represents a significant fraction of the total precipitating area. The observed temperature, wind, and moisture fields in the TEPPS case study as well as in statistical composites of radiosonde and global reanalysis data suggest that the stratiform component plays an essential role in the dynamics of convectively coupled Kelvin waves. Several idealized theories of coupled wave instability are compared with these observed structures.

A new mechanism for the initiation of convectively coupled Kelvin waves is presented in this study. During austral winter (boreal summer), a baroclinic Rossby wave packet excited in the Southern Hemisphere subtropical jet is associated with the initiation of a convectively coupled Kelvin wave in the central Pacific ITCZ. These results demonstrate that Kelvin waves can be forced from the extratropics even in regions of tropical easterlies.

Finally, convectively coupled Kelvin wave activity is shown to be modulated by the boreal summer intraseasonal oscillation (ISO). ISO convective anomalies force lowfrequency oscillations in the strength. location, and wave activity of the Southern Hemisphere subtropical jet, which modulates tropical Kelvin wave activity through changes in the extratropical forcing of these waves.
Keywords: atmosphere